THE REPRESENTATION OF MERU IN BALI’S TOURISM VISUAL BRANDING: SYMBOLISM, IDENTITY, AND COMMODIFICATION - Sindu Putra, Ida Bagus Komang; Adi Sakara, I Putu; Anadhi, I Made Gede; Suryawan, I Gede (UHN IGB Sugriwa Denpasar, 2025)
Meru is a dominant visual element in tourism branding, particularly in culturally based destinations such as Bali. This study aims to analyze how the form of Meru is represented in tourism visual branding and how this symbol contributes to shaping the identity of tourism destinations. Using a qualitative research approach that integrates visual analysis and semiotic studies, this research explores the symbolic meaning of Meru across various tourism promotional materials, including posters, brochures, social media, and official websites. Additionally, the study examines the commodification of spirituality, specifically how the use of Meru in Bali’s tourism branding can lead to the reduction of its religious significance, transforming it into a mere commercial icon. The findings indicate that Meru in tourism branding not only represents architectural beauty and cultural exoticism but also constructs a spiritual image that appeals to global tourists. However, the exploitation of this cultural symbol generates ambiguity among local communities, who perceive that the use of Meru in tourism promotion may shift its sacred value into a mere commercial attraction. Therefore, a balanced branding strategy is necessary to uphold cultural values while maintaining tourism appeal.